Piperlongumine, a Novel TrxR1 Inhibitor, Induces Apoptosis in Hepatocellular Carcinoma Cells by ROS-Mediated ER Stress - Zhang, Qianqian; Chen, Weiqian; Lv, Xiuling; Weng, Qiaoyou; Chen, Minjiang; Cui, Ri; Liang, Guang; Ji, Jiansong (Frontiers in Pharmacology, 2019)
Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third leading cause of cancer-related deaths globally. Despite advances in diagnosis and treatment, the incidence and mortality of HCC continue to rise. Piperlongumine (PL), an alkaloid isolated from the fruit of the long pepper, is known to selectively kill tumor tissues while sparing their normal counterparts. However, the killing effects of PL on HCC and the underlying mechanism of PL are not clear. We report that PL may interact with thioredoxin reductase 1 (TrxR1), important selenocysteine (Sec)-containing antioxidant enzyme, and induce reactive oxygen species (ROS)-mediated apoptosis in HCC cells. Our results suggest that PL induces a lethal endoplasmic reticulum（ER） stress response in HCC cells by targeting TrxR1 and increasing intracellular ROS levels. Notably, PL treatment reduces TrxR1 activity and tumor cell burden in vivo. Additionally, TrxR1 is significantly upregulated in existing HCC databases and available HCC clinical specimens. Taken together, these results suggest PL as a novel anticancer candidate for the treatment of HCC. More importantly, this study reveals that TrxR1 might be an effective target in treating HCC.